Extra‐cardiac diagnoses and postnatal outcomes of fetal tetralogy of fallot. (27th January 2022) - Sharma, Rishav; Niederhoffer, Karen Y.; Caluseriu, Oana; Cooke, Christy‐Lynn; Hornberger, Lisa K.; He, Rose; Eckersley, Luke; Lin, Lily; Rushfeldt, Michelle; McBrien, Angela
Abstract: Objective: Past studies of fetal tetralogy of fallot (ToF) have reported extra‐cardiac anomalies (ECAs) in 17%–45%, genetic syndromes in as low as 20% and poor postnatal outcomes. This study sought to examine these factors in a contemporary cohort. Methods: A retrospective review examining 83 fetuses with ToF diagnosed 2012–2019. Referral indication, ToF subtype, additional cardiac, extra‐cardiac and genetic diagnoses, pregnancy outcomes and survival were documented. Results: The mean gestational age at diagnosis was 23 ± 4 weeks. Of 94% (78/83) with genetic testing (GT), 30% (23/78, 95%CI 21%–40%) had genetic anomalies (GA), including Trisomy 21 (39%, 9/23), 22q11 deletion (35%, 8/23), Trisomy 13 or 18 (17%, 4/23) and 9% (2/23) others. A further 4% (3/78) had VACTERL association. Forty–one percent (34/83, 95%CI 31%–52%) had ≥1 major ECA of whom 41% (14/34) also had a genetic anomaly. Outcomes: 22% (18/83) pregnancy termination, 5% (4/83) intrauterine death and 72% (60/83) live birth. Of live births, 3% (2/60) experienced neonatal death, 7% late death (4/60) and 90% (54/60) were alive at last follow‐up (mean age 3.5 ± 2.4 years). Conclusion: In a cohort of fetuses with ToF and high rates of GT, compared to previous reports, GA were more common and there were similar rates of ECAs. Key points: What is already known about this topic? While tetralogy of fallot (ToF) can be an isolated finding, extra‐cardiac anomalies (ECAs) affecting major organ systems have been reported in 17%–45% of affected fetuses. Past investigations have suggested a genetic syndrome is present in 20%–40% of ToF cases. What this study adds? In a modern cohort with high rates of genetic testing, (GT) and postnatal follow‐up, 30% of cases with prenatally detected ToF had identifiable genetic aetiologies. Postnatal outcomes for live‐births with prenatally detected ToF have improved, with 90% alive on mid‐term follow‐up (mean age 3.5 ± 2.4 years). Despite improvements in prenatal detection, 41% with a prenatal diagnosis of ToF had one or more major ECAs.